Comparison Between Forehand and Backhand Stroke Techniques in the Accuracy of Strikes Among Extra-Curricular Table Tennis Students at State Senior High School 1 Sedayu - Wahyu Hidayat; Ardhika Falaahudin (Education Achievement: Journal of Science and Research, 2024)
This research is a descriptive study. The method used is a survey. The study population consists of 12 students participating in table tennis extracurricular activities at SMA Negeri 1 Sedayu. Data collection techniques employed in this research include testing and measurement. The results of the study indicate that (1) Forehand stroke abilities in table tennis extracurricular activities at SMA Negeri 1 Sedayu fall into the "high" category. When calculated as a percentage, the category with a very high level is 33.3%, comprising 4 students, the "high" category is 41% with 5 students, the "moderate" category is 16.6% with 2 students, and the "low" category is 8.3% with 1 student. There are no students in the "very low" category. (2) Backhand stroke abilities in table tennis extracurricular activities at SMA Negeri 1 Sedayu are categorized as "moderate". When calculated as a percentage, the "very high" category is 16.6%, with 2 students, the "high" category is 16.6%, with 2 students, the "moderate" category is 50%, with 6 students, the "low" category is 16.6%, with 2 students, and there are no students in the "very low" category.